Effect of Maleic Hydrazide and Waxing on Quality and Shelf-life of Mango (Mangifera indica L.) Fruits - Muddather, Aida Eesa; Abu-Goukh, Abu-Bakr A. (University of Khartoum Journal of Agricultural Sciences, 2023)
The effect of post-harvest treatment of maleic hydrazide (MH) with and without waxing on the quality and shelf-life of ‘Kitchner’ and ‘Abu-Samaka’ mango fruits at 18 ±1°C and 85% - 90% relative humidity was studied. Maleic hydrazide and wax treatments delayed fruit ripening, reduced losses, maintained quality and extended shelf-life of mango fruits. MH at 500 and 1000 ppm significantly delayed fruit ripening by two and four days in both mango cultivars, respectively, compared with the untreated fruits. The higher the concentration of MH, the more delay in fruit ripening. Waxing in addition to MH treatment resulted in ripening delay of six days in fruit ripening than treatment with MH alone. The effect of MH and waxing treatments in delaying mango fruit ripening, was indicated in retarded respiratory climacteric, reduced water loss, delayed peel colour development, fruit softening and total soluble solids accumulation and retained ascorbic acid content.